Revelation and Religious Experience: A critical study of René Latourelle’s theology of revelation - Aleksander Dancar (Journal of Asian Orientation in Theology, 2021)
This article is a critical study of René Latourelle’s concept of revelation who conceives of it as Word, testimony and encounter. The theological thesis that I would like to advance in this article is that, whatever the analogy of God’s revelation, it is always fundamentally rooted in the experience of human openness to the highest value of his/her life in this world. Revelation itself is the analogical word of the most significant human experience in the world. The historical intervention of God is always experienced symbolically and considered plausibly according to the criterion of universal reason. Every understanding of the mystery is a human experience which in its essence is conditioned by the mystery itself. In this sense, it can be said that every concept of revelation is constructed from any interpretative and significant experience of the human being. This fundamental aspect of Christian revelation does not appear in Latourell's theological reflection.